Development and Validation of Knowledge Test on Indigenous Alder based Jhum Cultivation and Mechanism for Knowledge Dissemination (Indian Journal of Extension Education, 2021)
Jhum cultivation has been blended in the tradition of hill’s tribes. Narrowing Jhum cycle has a devastating effect on the land and environment. In order to overcome the effect of Jhum cultivation, the famers of Khonoma village, Nagaland has indigenously developed very economical and unique model of Alder based Jhum cultivation with terrace farming on lower latitudes. To maintain the essence of this model, village developed Thesu group to transfer the knowledge from generation to generation. The present study aims at development of knowledge test to measure the level of knowledge about Alder based Jhum cultivation among the different age groups in Khonoma village, Kohima district, Nagaland. A set of 16 items were prepared and with content validation administered to randomly selected 45 farmers. Based upon the Item difficulty index and item discriminatory power, a set of 12 items was selected. Cronbach’s Alpha of 0.904 established its reliability and the validity was established with discriminant validity. The average knowledge was found to highest among young farmers who were actively involved in agricultural activities.